The usage, self-presentation via Facebook, and its psychological and sociological consequences towards Saudi Arabia University students / Abdullah Ali Alassiri - Alassiri, Abdullah Ali (Institute of Graduate Studies, UiTM, 2016)
Prompted by the widespread saturation of Facebook usage in Saudi Arabia, among university students to socialize with online members, this study investigated the usage, self-presentation, psychological and sociological consequences of the Facebook social networking site among undergraduate students in Saudi Arabia. The problem statements of this study were addressed by answering the seven research questions: 1) What motivation does undergraduate students have for joining Facebook? 2) How undergraduate students do consume Facebook? 3) In what condition does undergraduate students need Facebook? 4) How do undergraduate students manage their self-presentation via Facebook? 5) What are the experiences obtained by the undergraduate students from Facebook psychologically? 6) What are the experiences obtained by the undergraduate students from Facebook sociologically? 7) How have Facebook activities affected the lifestyle of the undergraduate students? The research questions were answered by analysing in-depth interview data collected from twenty male undergraduate students between the ages of 18 and 24 years selected from King Saud University (KSU) and King Khalid University (KKU) Saudi Arabia. Using thematicanalysis, informants data were coded ‘R1 to R20’, validated and was transcribed to minimize error from translating into the research items from Arabic back to English Language. Using purposive sampling method informant perspective within the research context were explored…